KOMPOSISI SENYAWA FENOL DAN POTENSI ANTIOKSIDAN DARI KACANG-KACANGAN: REVIEW - Nurud Diniyah; Sang-Han Lee (JURNAL AGROTEKNOLOGI, 2020)
Legumes are good dietary source of bioactive phenolic compounds which play significant roles in many physiological as well as metabolic processes. Flavonoids, phenolic acids and condensed tannins are the main phenolic compounds that are provide in legume seeds. Majority of the phenolic compounds are serving in the legume seed coats. The majority of seed coat of legume seeds are phenolic acids and flavonoids (mainly catechins and procyanidins). Gallic and protocatechuic acids are common in kidney bean and mung bean. Almost 70% of total phenolic compounds in lentils and cranberry beans (seed coat) are catechins and procyanidins. The antioxidant activity of phenolic compounds is in lineal intercourse with their chemical structures such as number as well as position of the hydroxyl groups. Processing mostly conducts to the alleviation of phenolic compounds in legumes because of chemical rearrangements. Phenolic content also lessen due to leaching of water-soluble phenolic compounds into the cooking water. This review provides comprehensive information of phenolic compounds identified in grain legume seeds along with discussing their antioxidant. Keywords: antioxidant activity, legume seeds, phenolic compounds, processing